4.20.3 \(y(x) y'(x)^2+(x-y(x)) y'(x)-x=0\)

ODE
\[ y(x) y'(x)^2+(x-y(x)) y'(x)-x=0 \] ODE Classification

[_quadrature]

Book solution method
No Missing Variables ODE, Solve for \(y'\)

Mathematica
cpu = 0.00580615 (sec), leaf count = 47

\[\left \{\left \{y(x)\to c_1+x\right \},\left \{y(x)\to -\sqrt {2 c_1-x^2}\right \},\left \{y(x)\to \sqrt {2 c_1-x^2}\right \}\right \}\]

Maple
cpu = 0.006 (sec), leaf count = 20

\[ \left \{ {x}^{2}+ \left (y \relax (x ) \right ) ^{2}-{\it \_C1}=0,y \relax (x ) =x+{\it \_C1} \right \} \] Mathematica raw input

DSolve[-x + (x - y[x])*y'[x] + y[x]*y'[x]^2 == 0,y[x],x]

Mathematica raw output

{{y[x] -> x + C[1]}, {y[x] -> -Sqrt[-x^2 + 2*C[1]]}, {y[x] -> Sqrt[-x^2 + 2*C[1]
]}}

Maple raw input

dsolve(y(x)*diff(y(x),x)^2+(x-y(x))*diff(y(x),x)-x = 0, y(x),'implicit')

Maple raw output

x^2+y(x)^2-_C1 = 0, y(x) = x+_C1